EFEKTIVITAS PELATIHAN EMPATI UNTUK MENINGKATKAN EMPATI PADA ANAK PELAKU PERUNDUNGAN - Ayuningtyas, Berliana; Nurhidayah, Siti; Duhita Pramintari, Ratna (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
Late childhood is often referred to as school or elementary school. With the age of 7-12 years, children still do not have good empathy with their classmates. Indonesia ranks first in the incidence of bullying in schools with 83%. One of the factors that can trigger bullying is a lack of empathy in children. Empathy is the ability to understand feelings, problems, and appreciate the differences in other people's feelings and think from their point of view. So that empathy training is considered an effective program to increase a person's level of empathy and reduce the level of aggression with affective and cognitive approaches. The purpose of this study was to determine the description of empathy in children who bullied, and to find out differences in behavior before and after being given treatment